Light-mediated control of activity in a photosensitive foldamer that mimics an esterase. Issue 18 (3rd February 2021) - Pollastrini, Matteo; Marafon, Giulia; Clayden, Jonathan; Moretto, Alessandro
Abstract : Photoisomerisation of a fumaramide/maleamide linker within a functionalised helical foldamer brings together a catalytic triad and activates catalytic esterase-like activity. Abstract : We report a catalytic foldamer in which a fumaramide chromophore links a Ser residue to a helical domain that contains within its sequence the residues His and Asp. Photoisomerization of the fumaramide chromophore (with E geometry) to the corresponding maleamide (with Z geometry) brings together a 'catalytic triad' of Ser, His, and Asp, triggering esterase activity that is absent in the fumaramide isomer. The fumaramide/maleamide linker thus acts as a light-sensitive switchable cofactor for activation of catalytic activity in short foldamers.